Achieving systems safety : proceedings of the Twentieth Safety-Critical Systems Symposium, Bristol, UK, 7-9th February 2012 - Dale, Chris 1953-; Anderson, Tom 1947- (Springer, 2012)
Achieving Systems Safety contains papers presented at the twentieth annual Safety-critical Systems Symposium, held in Bristol, UK, in February 2012. The Symposium is for engineers, managers and academics in the field of system safety, across all industry sectors, so the papers making up this volume offer a wide-ranging coverage of current safety topics, and a blend of academic research and industrial experience. They include both recent developments in the field and discussion of open issues that will shape future progress. The topics covered by the 20 papers in this volume include vulnerabilities in global navigation satellite systems; safety culture and community; transport safety; cyber-attacks on safety-critical systems; improving our approach to systems safety; accidents; assessment, validation and testing; safety standards and safety levels. The book will be of interest to both academics and practitioners working in the safety-critical systems arena.